Response of Fertilization with Goat Urine Fermentation Against the Growth of Leguminosa Indigofera (Indigofera zollingeriana) and Turi (Sesbania grandiflora) as animal feed ingredients in Samosir Regency - Sondang Siagian; Sayed Umar; Nurzainah Ginting; Tri Hesti Wahyuni; Hasnudi . (Jurnal Peternakan Integratif, 2018)
The need for animal feed in Pangururan District, Samosir Regency is very lacking, and livestock waste is also a problem in the community environment, so the utilization of EM4 goat's urine waste is expected to increase the growth of Indigofera (Indigofera zollingeriana) and Turi (Sesbania grandiflora) legumes in appropriate doses. . This research was conducted in Pangururan Subdistrict, Samosir Regency, North Sumatra from April to August 2018. The research design used in this research was factorial randomized block design (RBD) which was divided into 2 treatment groups and 3 replications. The first factor is the type of plant (L), L1 = Indigofera zollingeriana and L2 = Sesbania grandiflora and the second factor is the dose of fertilization (P), P0 = without fertilization (Control), P1 = 200 ml / polybag, P2 = 250 ml / polybag, P3 = 300 ml / polybag, and P4 = 350 ml / polybag). Parameters observed were plant height, number of stalks, number of leaves, and stem diameter. The results showed that respons of liquid organic fertilizer of goat urine fermented by EM4 with various doses of fertilization had a significant effect on the parameters of the study, namely plant height, number of stalks, number of leaves, and stem diameter. The conclusion of this study is that fertilization with a dose of 200 ml / polybag gives optimal results in the growth of Indigofera (Indigofera zollingeriana) and Turi (Sesbania grandiflora) legumes.